Displacement and education of the next generation: Evidence from Bosnia and Herzegovina - Christoph Eder (IZA Journal of Labor & Development, 2014)
In this paper, I study the effect of displacement (in the sense of forced migration) of parents during a violent conflict on investment in their childrens' education years later. Using the ethnic division during the Bosnian War as a natural experiment, I plausibly identify exogenously displaced households and compare them to households who did not have to move because of the war. Displaced parents spend between 20 and 30% less on the education of their children in primary and secondary school. The result also holds for single expenditure positions like textbooks, school materials and annual tuition in secondary school. A number of robustness checks and nearest-neighbor matching is performed to confirm the finding. A decomposition of the causal effect shows that differences in income and the stock of durable goods can at most explain one third of the finding. Potential explanations for the reduced spending of displaced parents on education include altered preferences through the exposure to violence, increased uncertainty about the future, and financial constraints.
Keywords: I25; J15; O15; 330; Displacement; Conflict; Education